Agro-chronobiology: Integrating circadian clocks /time biology into storage management. (June 2019) - Gottlieb, Daphna
Abstract: Almost all organisms on earth are adapted to anticipate daily environmental cycles and synchronize with these approximately 24-h rhythms by a circadian clock system. Given its importance to organismal success, the field of chronobiology is rapidly expanding unraveling the complex and integral role circadian clocks play. In applied science, these new insights have led to major advances mainly in the field of medicine. In the field of plant rearing and livestock management, the importance of circadian clocks is already acknowledged. Integrating circadian clocks in insect pest management has mainly received theoretical attention. Applying theory to practice is likely delayed because of the difficulty in managing an open environment. The storage environment is easier to control and therefore basic ideas of integrating circadian clocks to pest management could be applied. A cardinal difficulty in storage management is that storage insects develop resistance to common pesticides. This difficulty can be addressed by various manipulations of the insect's chronobiology. In this review, I discuss the various clock-driven behavioural, physiological and genomic processes that might be considered as sensitive targets for agro-chronobiology control. I further suggest that to promote the discipline of agro-chronobiology, the contribution of previous and current studies to the two following approaches in agro-chronobiology should be examined: 1) treating the vulnerable phases of the circadian clock, and 2) distorting the circadian clock system. Highlights: Agro-chronobiology (AgCb) is the integration of chronobiology to agriculture. AgCb approach includes distortion and synchronization of the circadian clock. Grain storage is a good model system to set the ground for the AgCb discipline. AgCb control can be a cheap method to reduce phosphine in use. Several clock-driven processes are sensitive targets for AgCb control.